Persepsi Pelaku Usaha Mikro, Kecil, dan Menengah terhadap Program Pelatihan Kewirausahaan dalam Meningkatkan Kapasitas Usaha - Andri Astuti; Maisarah Gusvita; Siti Nur Haliza; Puja Helisa Aulia; Vawziyah; Nurzannah; Tedi Saputra (Multiverse: Open Multidisciplinary Journal, 2026)
Micro, Small, and Medium Enterprises play a pivotal role in fostering economic growth and enhancing community welfare, yet many actors continue to encounter constraints related to limited entrepreneurial knowledge, inadequate managerial competencies, and low levels of business innovation. This study examines how Micro, Small, and Medium Enterprise actors perceive the effectiveness of entrepreneurship training programs in strengthening business capacity, while also identifying the factors shaping these perceptions and proposing strategies to improve program outcomes. A descriptive qualitative approach was employed, utilizing observation, in-depth interviews, and documentation involving participants of entrepreneurship training programs in Tenam Village, Muara Bulian District, Batang Hari Regency. The findings reveal that participants generally express positive perceptions, particularly regarding improvements in business management knowledge, business planning skills, and foundational understanding of financial management and Islamic economic principles. Perceptions are influenced by the relevance of training materials, instructional methods, prior participant experience, and the duration of training. The study argues that enhancing the alignment between training content and business needs, extending training duration and intensity, and ensuring sustained post-training assistance are critical to optimizing the effectiveness of entrepreneurship training programs in strengthening Micro, Small, and Medium Enterprise capacity.